Opiniowanie miejscowych planów zagospodarowania przestrzennego przez wojewódzkich inspektorów ochrony środowiska w związku z lokalizacją zakładów zagrożonych poważną awarią - Bukowski, Zbigniew (Studia Prawa Publicznego, 2022)
The article deals with the issuing of opinions on local spatial development plans by the voivodeship environmental protection inspector in connection with the location of plants at risk of a serious accident. The article analyses in detail the regulations in the aforementioned ﬁeld. The following conclusions were adopted: 1. Not in every case is the local spatial development plan referred to the voivode-ship environmental protection inspector for an opinion; 2. after the commune council adopts a resolution to begin drawing up the local plan, it is the commune head, mayor or city president that decides to apply to the voivodeship environmental protection inspector for an opinion on the draft plan, provided that the plan allows the location of plants posing a risk of a serious in-dustrial accident; 3. should the head of the commune, mayor or president not request that the voivodship environmental protection inspector issue an opinion on the draft plan, this will constitute a violation of the plan preparation procedure if the plan allows the location of plants posing the risk of a serious industrial accident; 4. issues related to the deadline for giving an opinion and its extension are regu-lated in the Act on Spatial planning and development, which regulations constitute a lex specialis to the Code of Administrative Procedure; 5. any failure by the commune head, mayor, city president to take into account the negative opinion of the voivodeship environmental protection inspector, based on speciﬁc regulations concerning the location of plants posing the risk of a serious industrial accident, is a violation of the law.